(untitled) (Research, Society and Development, 2021)
In Chemical Engineering Unit Operations, among the countless pieces of equipment that can be used in the stage of separation of unwanted solids, those that contain added value are in the elutriators. The operation of these equipment is based on the difference in size and/or density of the particles fed into the system, which are retained in any equipment or are carried by the drag fluid, depending on the physical characteristics. Elutriators are usually operated in series and are widely used in the mining industry. This study aims to analyze the behavior of three elutriators in series, separate the fed particles if they differ in size and density, using Scilab as the main tool. When studying the behavior of the system in face of the variation of the alpha (α), minimum fluidization velocity (Umf) and system flow (Q) parameters, the influence of changes in the variables of mass retained in the bed (W (ri)) and elutriation constant (k (ri)) were analyzed.